A new method of styrene-butadiene rubber curing using in situ generated Lewis acids - Dmowska-Jasek, P.; Rzymski, W. M.; Koścista, E.; Bociong, K. (Polimery, 2015)
Heating of blends composed of styrene-butadiene rubber (SBR) and chlorosulphonated polyethylene (CSM) at T = 453 K in the presence of fine powdered Zn leads to curing of the elastomers involving interelastomer reactions of the blend components. Analysis of IR spectra leads to the conclusion that the curing in the studied blends is a result of the interelastomer Friedel-Crafts alkylation of the SBR phenyl rings with the elastomeric polyhalide. This reaction is catalyzed with a Lewis acid (ZnCl2) generated in situ by the reaction of CSM with the Zn powder. This new, unconventional method can be used for the curing of the SBR/CSM blends containing selected fillers.